INCREASING THE CREATIVITY OF NATURAL SCIENCES IN THE WATER CYCLE MATERIALS THROUGH A CONTEXTUAL APPROACH IN GRADE 5 MI YAA BUNAYYA - Anis Farahanim Abd Rahman; Fajar Dwi Mukti (Fakultas Tarbiyah, IAIN Fattahul Muluk Papua, 2022)
The aims of this study were: To increase the creativity of science learning on the water cycle material through a contextual approach to fifth-grade students at MI Yaa Bunayya. This type of research is a class action research of 2 cycles. Each cycle consists of 4 stages: planning, implementation of the action, observation, and reflection. The research subjects were fifth-grade students at MI Yaa Bunayya. Data collection techniques using observation. There is an increase in student creativity, as indicated by the rise in student attitudes when participating in learning in each cycle. Cycle I, with a percentage of 65%, includes sufficient criteria. Cycle II obtained a percentage of 8 7.5% with creativity criteria very good. Contextual can increase the creativity of science learning on the water cycle material through a contextual approach to grade 5 MI Yaa Bunayya